Customers’ Perception Towards Internet Banking Services - Selvam, V. (Indian Journal of Computer Science, 2017)
The key players of the banking industry are its customers and all the efforts made by banks are to satisfy the needs of the customers The entry of internet affected our daily lives and most dimensions of our lives such as education, communication, business, etc. are overshadowed by this novel phenomenon. The main objectives of the present study were to evaluate the level of awareness of internet banking services among customers of commercial banks, to identify various factors influencing the usage of internet banking services, and to measure the level of satisfaction with internet banking services among the customers of commercial banks. This study concluded that awareness about and satisfaction of customers for e-banking services leads to improvement of smart banking operations and applications of technological advancements. The levels of satisfaction with internet banking services are viewing account balance, online bill payment, and RTGS in internet banking services.